Mechanism of tumour vascularization in experimental lung metastases. Issue 3 (18th December 2014) - Szabo, Vanessza; Bugyik, Edina; Dezso, Katalin; Ecker, Nora; Nagy, Peter; Timar, Jozsef; Tovari, Jozsef; Laszlo, Viktoria; Bridgeman, Victoria L; Wan, Elaine; Frentzas, Sophia; Vermeulen, Peter B; et al.
Abstract The appearance of lung metastases is associated with poor outcome and the management of patients with secondary pulmonary tumours remains a clinical challenge. We examined the vascularization process of lung metastasis in six different preclinical models and found that the tumours incorporated the pre‐existing alveolar capillaries (ie vessel co‐option). During the initial phase of vessel co‐option, the incorporated capillaries were still sheathed by pneumocytes, but these incorporated vessels subsequently underwent different fates dependent on the model. In five of the models examined (B16, HT1080, HT25, C26, and MAT B‐III), the tumour cells gradually stripped the pneumocytes from the vessels. These dissected pneumocytes underwent fragmentation, but the incorporated microvessels survived. In the sixth model (C38), the tumour cells failed to invade the alveolar walls. Instead, they induced the development of vascularized desmoplastic tissue columns. Finally, we examined the process of arterialization in lung metastases and found that they became arterialized when their diameter grew to exceed 5 mm. In conclusion, our data show that lung metastases can vascularize by co‐opting the pulmonary microvasculature. This is likely to have important clinical implications, especially with respect to anti‐angiogenic therapies. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. .